Mitochondrial apoptosis in response to cardiac ischemia-reperfusion injury - Kaixin Wang; Qing Zhu; Wen Liu; Linyuan Wang; Xinxin Li; Cuiting Zhao; Nan Wu; Chunyan Ma (Journal of Translational Medicine)
Abstract In patients with acute myocardial infarction (AMI), thrombolytic therapy and revascularization strategies allow complete recanalization of occluded epicardial coronary arteries. However, approximately 35% of patients still experience myocardial ischemia/reperfusion (I/R) injury, which contributing to increased AMI mortality. Therefore, an accurate understanding of myocardial I/R injury is important for preventing and treating AMI. The death of each cell (cardiomyocytes, endothelial cells, vascular smooth muscle cells, cardiac fibroblasts, and mesenchymal stem cells) after myocardial ischemia/reperfusion is associated with apoptosis due to mitochondrial dysfunction. Abnormal opening of the mitochondrial permeability transition pore, aberrant mitochondrial membrane potential, Ca2+ overload, mitochondrial fission, and mitophagy can lead to mitochondrial dysfunction, thereby inducing mitochondrial apoptosis. The manifestation of mitochondrial apoptosis varies according to cell type. Here, we reviewed the characteristics of mitochondrial apoptosis in cardiomyocytes, endothelial cells, vascular smooth muscle cells, cardiac fibroblasts, and mesenchymal stem cells following myocardial ischemia/reperfusion.